2022
DOI: 10.3390/nano12020195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aluminum Doping Ratios on the Properties of Aluminum-Doped Zinc Oxide Films Deposited by Mist Chemical Vapor Deposition Method Applying for Photocatalysis

Abstract: Aluminum-doped zinc oxide film was deposited on a glass substrate by mist chemical vapor deposition method. The influence of different aluminum doping ratios on the structural and optical properties of zinc oxide film was investigated. The XRD results revealed that the diffraction peak of (101) crystal plane was the dominant peak for the deposited AZO films with the Al doping ratios increasing from 1 wt % to 3 wt %. It was found that the variation of AZO film structures was strongly dependent on the Al/Zn rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…One of the most promising alternatives to indium tin oxide (ITO) is zinc oxide (ZnO) since the elements are easily available and that are also safe and reliable throughout the process of designing. Pulsed laser deposition [2], atomic layer depsoiton [3], magnetron sputtering [4,5], chemical vapour deposition [6], sol-gel dip coating [7] and sol-gel spin coating [8] are only some of the methods that can be used to synthesize it. Zinc oxide (ZnO) is an n-type semiconductor with a broad direct band gap (3.37 eV) in the near-UV spectral region and great chemical stability; nevertheless, its high resistivity prevents it from being widely used in thermochromic elements (TCEs).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most promising alternatives to indium tin oxide (ITO) is zinc oxide (ZnO) since the elements are easily available and that are also safe and reliable throughout the process of designing. Pulsed laser deposition [2], atomic layer depsoiton [3], magnetron sputtering [4,5], chemical vapour deposition [6], sol-gel dip coating [7] and sol-gel spin coating [8] are only some of the methods that can be used to synthesize it. Zinc oxide (ZnO) is an n-type semiconductor with a broad direct band gap (3.37 eV) in the near-UV spectral region and great chemical stability; nevertheless, its high resistivity prevents it from being widely used in thermochromic elements (TCEs).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5a demonstrates the model of the growth process of the AZO/ZnO core-shell nanorods at 400 • C during the mist CVD method. The mechanism of growth of AZO film using the mist CVD process was already revealed in our previous research [25,29]. As shown in Figure 5a, the generated mist droplets, including zinc acetate (ZA)and aluminum acetylacetonate (AA), were transported to the reaction chamber, in which ZnO nanorods were heated and kept at 400 • C. During the AZO coating process, the transported mist droplets could be decomposed and release Al and Zn ions on the ZnO nanorods; the AlO 6 bonding mode could occur when the deposition temperature was over 350 • C during the mist deposition process, and the released Al ions could be bonded with oxygen and form Al x O 1−x .…”
Section: Resultsmentioning
confidence: 64%
“…A large bandgap can enhance the separation of charge carriers, reducing the recombination rate of electron–hole pairs. In our previous research [ 25 ], Al was effectively doped in ZnO thin film with precise and controllable doping ratios by using the mist chemical vapor deposition (CVD) method, resulting in enlarged bandgap energy. However, the resultant low crystallinity of AZO film remained a subject of concern.…”
Section: Introductionmentioning
confidence: 99%
“…The low-magnification TEM micrographs (left column) revealed that the AZO nanostructures changed from rounded aluminum that can induce lattice distortion in ZnO, leading to a reduction in crystallinity. 48 Overall, the results demonstrated that TMA exposure time is a crucial factor in controlling the AZO growth, morphology, and crystallinity. 13 intentionally fabricated, such that resistance vs channel length data can be acquired.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 78%